When Success Isn't Everything - Case Studies of Two Virtual Teams - Jarman, Rod (Springer-Verlag Dordrecht, 2005)
Researchers have been attempting to identify the factors that contribute to virtual team success. Two virtual teams were studied over six-months using an interpretive approach and qualitative data collection techniques. The outcomes of these teams were outwardly very poor. Yet, team members considered themselves successful in relation to the circumstances in which they found themselves. The team members identified the factors they believed contributed to the outcomes and the rationale for why they were successful despite the outward appearances. The interpretive approach allowed for an exploration of the circumstances, and how these perspectives were derived. The cases indicate that working in distributed mode can be problematic if teamwork issues are not addressed and a technological focus adopted.